In situ U-Pb zircon age determination on plagioclase porphyry dike from Siilinjärvi - Hurttila, Vilma (My University, 2025)
U-Pb isotopic dating provides a reliable method to determine the timing of magmatic and metamorphic events. Zircon is an ideal mineral for U-Pb geochronology due to its durability and uranium-accommodating crystal structure. Finnish Precambrian bedrock records a long and complex geological history, with the boundary between the Archean Karelia Province and the Svecofennia Province providing valuable insights into crustal evolution processes. The Siilinjärvi carbonatite Complex, located within the Archean rocks of eastern Finland near the Svecofennian boundary, represents one of the world's oldest carbonatites (~2.61 Ga). Understanding the timing and nature of later magmatic events in the region is crucial for interpreting the complex crustal evolution involving Archean structures and Proterozoic overprinting. This study focuses on determining the crystallization age of a plagioclase porphyry dike from the Siilinjärvi apatite mine, interpreted as the youngest magmatic phase in the immediate area. The aim is to determine the emplacement age of this dike and to understand its genesis and implications for the geological evolution of the region. In situ U-Pb geochronology was performed on zircons extracted from the plagioclase porphyry dike using LA-ICPMS. Detailed petrographic studies using optical microscopy and whole-rock geochemical analyses were conducted on the porphyry dike and three comparative rock samples from the Muuruvesi suite. The U-Pb dating of the plagioclase porphyry yielded a concordia age of 1900 ± 14 Ma from analyses of the outermost zircon rims. The zircon population was complex, also containing abundant older, inherited Archean cores (predominantly 2.5−2.8 Ga) and a Paleoproterozoic age population (2.07−2.30 Ga). Geochemically, the plagioclase porphyry is distinct from the Muuruvesi suite samples, characterized by higher alkali content (Na2O+K2O). In contrast, the Muuruvesi suite samples are geochemically similar to quartz-diorites, tonalites and granodiorites used as a reference group from the area. All investigated samples display significant low-grade metamorphic alteration features, including sericitization, saussuritization, and the formation of epidote-group minerals and chlorite. The plagioclase porphyry exhibits additional replacement of plagioclase by K-feldspar and calcite. The 1900 ± 14 Ma age obtained for the plagioclase porphyry is interpreted in two ways: it may represent Svecofennian crystallization age, supported by magmatic zoning in zircon rims and temporal alignment with Svecofennian collisional events. Alternatively, it could record Svecofennian metamorphic overprint on an older intrusion as suggested by the upper intercept of a discordia line at 2584 ± 27 Ma and the low Th/U ratios (0.026–0.072) in the youngest zircon rims, which are characteristic of metamorphic zircon. Further research specifically U-Pb crystallization dating of the Muuruvesi suite samples, is essential to resolve the emplacement age of the plagioclase porphyry dike and to provide more understanding of the Svecofennian orogenic events and their impact on the Siilinjärvi area.

U-Pb isotooppi-ikämääritysmenetelmä on luotettava tapa määrittää magmaattisten ja metamorfisten tapahtumien ajankohta. Zirkoni on erinomainen mineraali U-Pb geokronologiassa sen kestävyyden sekä uraania sitovan kiderakenteen vuoksi. Suomen kallioperällä on pitkä ja monimutkainen geologinen historia ja arkeeisen Karjalan provinssin sekä Svekofennian provinssin välinen raja tarjoaa arvokasta tietoa kuoren kehitysprosesseista. Siilinjärven karbonatiittikompleksi, joka sijaitsee Itä-Suomen arkeeisella kallioperällä lähellä Svekofennian rajaa, edustaa yhtä maailman vanhimmista karbonatiiteista (n. 2,61 Ga). Myöhempien magmaattisten tapahtumien ajoituksen ja luonteen ymmärtäminen on tärkeää tulkittaessa monimutkaista kuoren kehitystä, johon liittyy arkeeisia rakenteita ja proterotsooista uudelleenmuokkausta. Tämä tutkimus keskittyy Siilinjärven apatiittikaivoksella sijaitsevan plagioklaasiporfyyrijuonen kiteytymisiän määrittämiseen, jonka tulkitaan olevan lähialueen nuorin magmaattinen vaihe. Tavoitteena on määrittää juonen intruusioikä sekä ymmärtää sen syntyä ja merkitystä alueen geologiselle kehitykselle. Plagioklaasiporfyyrijuonesta erotetuille zirkoneille tehtiin in situ U-Pb-geokronologinen ajoitus käyttäen LA-ICPMS-menetelmää. Juonelle ja kolmelle vertailtavalle mikrotonaliittiselle Muuruveden sarjan kivinäytteille tehtiin petrografiset tutkimukset optisella mikroskopialla sekä kokokivigeokemialliset analyysit. Plagioklaasiporfyyrin U-Pb-ajoitus tuotti zirkonien uloimmilta reunoilta analysoidun konkordia-iän 1900 ± 14 Ma. Zirkonipopulaatio oli monimutkainen, sisältäen myös runsaasti vanhempia, perittyjä arkeeisia ytimiä (pääasiassa 2,5–2,8 Ga) sekä paleoproterotsooisen ikäryhmän (2,07–2,30 Ga). Geokemiallisesti plagioklaasiporfyyri eroaa Muuruveden sarjan näytteistä korkeamman alkalipitoisuutensa (Na2O+K2O) perusteella. Sen sijaan Muuruveden sarjan näytteet ovat geokemiallisesti samankaltaisia alueen vertailuryhmänä käytettyjen kvartsidioriittien, tonaliittien ja granodioriittien kanssa. Kaikissa tutkituissa näytteissä on havaittavissa merkittäviä matalan asteen metamorfisia muuttumispiirteitä, kuten serisiittiytymistä, saussuriittiytymistä sekä epidoottiryhmän mineraalien ja kloriitin muodostumista. Plagioklaasiporfyyrissä esiintyy lisäksi plagioklaasin korvautumista kalimaasälvällä sekä kalsiittia. Plagioklaasiporfyyrille saatua 1900 ± 14 Ma:n ikää voidaan tulkita kahdella tavalla: se voi edustaa svekofennistä kiteytymisikää, mitä tukevat zirkonien reunojen magmaattiset kasvuvyöhykkeet ja ajallinen yhteys svekofennisiin orogeenisiin tapahtumiin. Vaihtoehtoisesti ikä voi kuvastaa svekofennistä metamorfista vaikutusta vanhempaan intruusioon, mitä tukee diskordian ylempi leikkauspiste 2584 ± 27 Ma:ssa sekä nuorimpien zirkonireunojen matalat Th/U-suhteet (0,026–0,072), jotka ovat tyypillisiä metamorfisille zirkoneille. Jatkotutkimukset, erityisesti Muuruveden sarjan näytteiden U-Pb-kiteytymisikien ajoittaminen, olisivat tärkeitä plagioklaasiporfyyrijuonen iän selvittämiseksi ja Siilinjärven alueen svekofennisten orogeenisten tapahtumien ja niiden vaikutusten tarkemmaksi ymmärtämiseksi.
Keywords: U-Pb dating, zircon, plagioclase porphyry, Siilinjärvi, geochemistry, U-Pb-ikämääritys, zirkoni, plagioklaasi porfyyri, Siilinjärvi, geokemia